Tablet as a training material: Contribution of content diversity to education rate - SEMIH DELIL (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The study’s overarching objective was to investigate how people use tablet computers.Method: As part of the screening model used in this study, interviews with professionals in the field were conducted. Twenty students will be randomly selected from the study group’s visual roster.Findings: In this study, we found that as technology has advanced, the demand for tablet computers has also grown. These gadgets have a variety of uses, including education, business, and leisure. They worked very well as training materials when used on computers. More and more often, people’s preferences are influenced by factors such as when and where they received their education. Communicating with the user in multiple ways (visually, aurally, and physically), these gadgets make it possible for students to learn in a way that best suits them, wherever they may be, at whatever time of day. Tablets, equipped with purpose-built educational software, can be used in the same environment as traditional classroom instruction, allowing for more focused learning.Implications/Novel Contribution: The findings can be used to promote a greater understanding of the potential of education in the classroom. Students should use the findings to deepen their expertise in computer-based networking and problem-solving.